Polyanalytical functions of constant modulus - Balk, M. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. Б. Балк. Полианалитические функции постоянного модуляM. Balk. Pastovaus modulio polianalizinės funkcijos